Description of the Targeted Jobs Tax Credit and S. 1250 Scheduled for a Hearing. - United States. Congress. Joint Committee on Taxation; United States. Congress. Senate. Committee on Finance. Subcommittee on Savings, Pensions, and Investment Policy (Washington : U.S. G.P.O., 1985)
Considers S. 1250.
Reuse of record except for individual research requires license from Congressional Information Service, Inc.
"Nov. 21, 1985."
CIS Microfiche Accession Numbers: CIS 85 S362-43
CIS Index 1985
Microfiche.
Mode of access: Internet.
Keywords: New jobs tax credit -- Law and legislation -- United States; Employment tax credit -- Law and legislation -- United States